Neuroimaging Techniques in Diagnosing and Understanding Neuromuscular Junction Disorders - Rasha Saad Mahmood Aldoury,; Lubna Al-Gailani,; Ali Al-Kaleel, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Neuromuscular junction (NMJ) disorders, which impaired communication between motor neuron and skeletal muscle, leading to muscle weakness and paralysis. Accurate diagnosis of these conditions remains challenging due to their varied etiology and clinical presentation. This article focuses on the role of neuroimaging in enhancing the diagnosis and understanding of NMJ disorders. Advances in imaging technologies, including magnetic resonance imaging (MRI), computed tomography (CT), and functional MRI (fMRI), provide detailed insights into the structure and function of NMJs. Allowing for improved identification of pathological changes. These image modalities offer non-invasive approaches that complement traditional diagnostic techniques, enabling earlier and more precise detection of NMJs disorders. The integration of these advanced methods into clinical practice improves patient outcomes by facilitating timely and accurate diagnosis. Despite the progress in neuroimaging, challenging remain, particularly in standardization and interpretation of results across different techniques. Future developments in imaging technology are expected to overcome these hurdles, paving the way for more effective diagnosis and treatment of NMJ disorders.